A Short-Term Feeding of Dietary Casein Increases Abundance of Lactococcus lactis and Upregulates Gene Expression Involving Obesity Prevention in Cecum of Young Rats Compared With Dietary Chicken Protein - Zhao, Fan; Song, Shangxin; Ma, Yafang; Xu, Xinglian; Zhou, Guanghong; Li, Chunbao (Frontiers in Microbiology, 2019)
Casein and chicken are assessed to contain high quality proteins, which are essential for human health. Studies have shown that ingestion of the two dietary proteins resulted in distinct effects on physiology, liver transcriptome and gut microbiota. However, its underlying mechanism is not fully understood, in particular for a crosstalk between gut microbiota and host under a specific diet intervention. We fed young rats with casein or chicken protein-based diet for 7 days, and characterized fast responses of cecal microbiota and cecal gene expression. We found that a short-term intervention with casein-based diet induced a higher relative abundance of beneficial bacterium Lactococcus Lactis as well as Bifidobacterium pseudolongum, and has a higher expression of genes involved in obesity associated pathways (e.g adipoq and Irs1) compared with chicken protein-based diet, which was reported to play an important role in protecting development of obesity. What’s more, the differential bacteria Lactococcus Lactis was positively associated with these differentially expressed genes in the gut tissue. Our results provide a new insight into the crosstalk between gut microbiota and host in response to dietary proteins, indicating a potential mechanism of obesity prevention function by casein.